THE INSTITUTIONAL MODEL OF PALM DOWNSTREAM INDUSTRY DEVELOPMENT - Suharjito Suharjito; Marimin Marimin (Jurnal Teknobisnis, 2012)
Abstract The palm oil industry is one of the leading sector in Indonesia and its contribution to national non-oil export is significantly large. Indonesia palm oil industry has also increased together with world demand for palm oil enhancement. The average growth rate of plantation area is 15% or equal to 200,000 hectare per year. Meanwhile, the palm production in Indonesia has reach 17 million tons in 2005 or increased 63.7% compare with year 2003 was 10.4 million tons only. The growth of downstream industries are not as fast as growth of palm oil industry itself, as a result the palm oil selling price is low and there is no added value from the downstream industry. The purpose of this study is to formulate a model of institutional development of downstream palm oil industry which appropriate based on various criteria and assessment of expert opinion. MPE method has been applied for this study in order to choose the most appropriate downstream industry in Indonesia. Then, the ISM method is also been used to formulate institutional models of efficient downstream palm oil industry. Finally, the AHP method has been adopted as well in order to select the development strategy of downstream palm oil agro-industry. The result of this study is the institutional element downstream palm oil industry has significantly affluence the development of oil palm industry as well as development strategy of Indonesia’s palm oil downstream industry.